1992
DOI: 10.1161/01.hyp.19.6.639
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide in noradrenergic transmission in rat hypothalamus.

Abstract: In the present study, we examined the regulatory mechanisms of calcitonin gene-related peptide on norepinephrine release in rat hypothalamus. Calcitonin gene-related peptide inhibited the stimulationevoked norepinephrine release from hypothalamic slices of Sprague-Dawley rats in a dose-dependent manner, although the peptide did not affect basal release of norepinephrine. The blockade of the o?2-adrenergic receptors by RX 781094 failed to modulate the inhibitory effects of calcitonin gene-related peptide on nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Another possible explanation is the myriad potentiating effects of cotransmitters released from adrenergic terminals within the heart such as CGRP, neuro- peptide-Y, and galanin (1,29). These neuropeptides are known to modulate NE and acetylcholine release (4,12,30,31) and may have a variety of effects on myocardial excitability under normal and pathological conditions. Dispersion of repolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation is the myriad potentiating effects of cotransmitters released from adrenergic terminals within the heart such as CGRP, neuro- peptide-Y, and galanin (1,29). These neuropeptides are known to modulate NE and acetylcholine release (4,12,30,31) and may have a variety of effects on myocardial excitability under normal and pathological conditions. Dispersion of repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether these single-nucleotide polymorphisms would be associated with disparate responses in repolarization heterogeneity during states of heightened sympathetic tone. Other factors that may contribute to this phenomenon include neuropeptide cotransmitters, which may affect myocardial excitability directly or indirectly (4,12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that CGRP may regulate the electrolyte and fluid secretion in the epididymis, thereby providing an optimal microenvironment for the maturation and storage of the spermatozoa [27]. CGRP further inhibits the release of norepinephrine [28]which was previously reported to be released in excessive amounts in contralateral testis during unilateral testicular torsion [29]. The administration of capsaicin may have further released CGRP and caused dilatation of the vessels thus contributed to the preservation of blood flow to the contralateral testis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study we presented previously, the changes in norepinephrine release induced by CGRP was investigated in the rat central nervous system. 2 In an in vitro study, we showed that CGRP inhibited the stimulationevoked norepinephrine release in a dose-dependent manner. It was also demonstrated that a dihydropyridine-sensitive calcium channel agonist, Bay K 8644, significantly reversed the inhibitory effect of CGRP on norepinephrine release, indicating that CGRP might partially interact with dihydropyridine-sensitive calcium channels and modulate intracellular calcium mobilization.…”
Section: To the Editormentioning
confidence: 94%